Relationship between Neuromuscular Mechanisms with Dynamic Balance and Upper Extremity Function of Wrestlers - Tabasi, Seyyed Reza; Norasteh, Aliasghar; Mirzaei, Bahman; Zarei, Hamed (Journal of Clinical Physiotherapy Research, 2018)
Introduction: Wrestling is always accompanied by damage to various body parts. Most trainers recommend exercises to increase balance in order to improve performance and reduce the risk of injury. Therefore, the present study examines the relationship between neuromuscular mechanisms with dynamic balance and upper extremity function of wrestlers. Materials and Methods: This is a correlation study whose participants include free-style and Greco-Roman wrestlers of 21.05±2.25 years old in Rasht. This study was conducted on 42 wrestlers who met the criteria to enter the research and were selected by the available sampling method. In this study, in order to evaluate the dynamic balance and the upper extremity function, Y Balance Test and Upper Quarter Y-Balance Test (YBT-UQ) were used, respectively. In addition, to measure the depth of shoulder flexion, ankle plantar flexion, shoulder flexion amplitude, and ankle plantar flexion, and to assess the strength of shoulder flexion force, ankle plantar flexion, muscle flexion of shoulder, and ankle plantar flexion, an electrogonimeter device and a dynamometer were used, respectively. Pearson correlation coefficient and multivariate regression were used to study the research hypotheses. Results: The results show that there is a significant positive relationship between the range of motion of ankle plantar flexion (r=0.64) and the normalized power of plantar flexors (r=0.85) with lower limb dynamic balance (P=0.03). There is also a significant negative relationship between the sensory errors of ankle plantar flexors force (r=-0.84) and the reconstruction of ankle plantar flexion (r=-0.85) with the lower limb dynamic balance (P=0.02). Moreover, the results show that there is a significant positive relationship between the range of motion of the Shoulder flexion (r=0.71) and the normalized power shoulder flexor (r=0.74) with upper limb function (P=0.001). There is also a significant negative relationship between the sensory error of shoulder flexor (r=-0.72) and the sense of reconstruction of shoulder flexion angle (r=-0.75) with upper limb function (P=0.03). Conclusion: It appears that the neuromuscular mechanisms are effective factors in upper extremity function and dynamic balance of wrestlers. Therefore, consideration of these neuromuscular mechanisms is necessary to prevent injury and improve wrestlers' athletic performance. Keywords: Wrestling; Dynamic Balance; Upper Extremity Function